Estudio analítico de los documentos de trabajo del parlamento europeo - Martín González, Yolanda (Revista General de Información y Documentación, 2002)
The European Parliament is the institution which represents civilian interests within the framework of the European Union. As such, but above all, on account of its being the only organ of an assembly type nature for the community, it generates series of documents of very defined characteristics.The reduced number of studies carried out in our country concerning the working documents of the European Parliament causes difficulties, not only to research workers, who inevitably have to come to grips with the complex informational map of the European Parliament whatever aspect of this institution they may study, but also to all the professionals who, in the university sphere, attempt to bring our students into contact with the bibliographic-documentary repertory of the Union.These are the reasons for offering a descriptive analysis of the principal documents generated by the institution which are to be presented, debated and either approved or rejected by the European Parliament.
Keywords: European Parliament; Parliamentary documentation